METODE PEMBELAJARAN BACA TULIS ALQUR’AN DI SMP ISLAM UNGARAN - Rudjiono; Achmad Zainudin; Ismail (STEKOM PRESS, 2020)
Basically, the principles of Al-Qur'an learning can be carried out using various methods, all of which have the same goal, namely so that children can read the Al-Qur'an properly and correctly. The low motivation of students in learning the Qur'an is still one of the reasons for the low quality of education, especially in the ability to read the Qur'an. One of the efforts to increase motivation to learn to Read and Write the Qur'an is the use of online methods during the Covid-pandemic. 19 can be carried out by educators or teachers in the reading and writing subject of the Koran which is the basis of learning in Islam The low motivation of students in learning Al-Qur'an is still one of the reasons for the low quality of education, especially in the ability to read Al-Qur'an. So it can be said that motivation and learning achievement are directly proportional to the learning methods developed. One of the efforts to increase the motivation to learn to read and write al-quran is to use appropriate methods that can be used by educators or teachers in reading and writing al-Qur'an subjects which are the basis of learning in Islam.